Analysis of the changing determinants of liquidity risk in U.S banks between 2007 and 2018 - QIAN, Jianan (2020)
The basic functions of banks are to take deposits and make loans, which make them vulnerable to unexpected cash outflows. If it is not well managed, liquidity risk will occur. Liquidity risk can cause considerable losses to banks and even lead to bankruptcy. The financial crisis of 2007 proved the destructive effect of liquidity risk and, since then, managing liquidity risk has become one of the main tasks of global commercial banks. This dissertation studies whether the determinants of the liquidity risk of U.S banks change over time in order to find out effective methods for liquidity risk management. For the empirical analysis, the quantitative method of panel data regression will be adopted. It turns out that the liquidity risk of U.S banks does change over time, shifting from deposits, to capital adequacy, and finally a combination of deposits, GDP and capital adequacy from 2007 to 2018. Finally, based on the obtained determinants of liquidity risk, some suggestions on liquidity risk management are put forward for U.S banks. It is expected that these empirical results can provide some enlightenment for banks and regulators to monitor liquidity risk to some extent.